PENGAWASAN SATUAN POLISI PAMONG PRAJA PADA PEDAGANG KAKI LIMA DI KECAMATAN BANGKO KABUPATEN ROKAN HILIR - Afrizal Afrizal; Meyzi Heriyanto; Febri Yuliani (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2023)
ABSTRACT The purpose of this study was to determine and describe the implementation of the duties of the Civil Service Police Unit in controlling street vendors in Bangko District, Rokan Hilir Regency and to find out the obstacles in carrying out the duties of the Civil Service Police Unit in controlling street vendors in Bangko District, Rokan Hilir Regency. The type in this research is a descriptive form, namely the type of research that describes the variables studied in research and quantitative form, namely research in the form of percentages and ends with drawing conclusions and giving suggestions. This research was conducted at the Civil Service Police Unit Office located in Batu 6 Office Complex. The types and sources of data collected in this study consisted of primary data and secondary data. From the description of the results of the recapitulation of the results of the research, both through the distribution of questionnaires and interviews, it can be concluded that the influence of the Civil Service Police Unit, Bangko District, Rokan Hilir Regency in maintaining public order in Bangko District, Rokan Hilir Regency (the study of Street Vendors) was carried out in a fairly good category.